PROSES PEMBENTUKAN SIKAP SECARA BERJENJANG: STUDI EMPIRIS DI BIDANG PERLUASAN MEREK - Budhi Haryanto (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This study examines goodness-of-fit model to explain brand extension phenomenon. Specifically, explaining the influence of brand similarity, belief toward core brand, and motivation to elaborate information on attitude toward brand extension. Laboratory experiment was used to ascertain controlled variables. Participants consist of 598 undergraduate students in business. Hierarchical regression analysis was used to elaborate the linkage among these observed variables. The study shows that complexity of brand extension was linearly influenced by brand similarity, belief toward core brand, and motivation to elaborate information. The finding confirms that the decision toward brand extension was significantly tested. Implications for further research are also discussed.